Inorganic silicon deep permeable crystallization waterproof agent and preparation process thereof

By adding active sodium silicate, nanocomposite particles and aluminate cement to the inorganic silicone waterproofing agent, combining the modified zinc oxide particles and specific dispersant to form a composite structure, the existing inorganic silicone waterproofing agent is solved. The problems of shallow penetration depth and poor stability achieve efficient deep penetration and long-term durability.

CN119462059AActive Publication Date: 2025-02-18FOSHAN JIAOYOU BUILDING MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411713926.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The penetration depth of existing inorganic silicone waterproofing agents in concrete is shallow, and the waterproofing effect is weakened after long-term use, and the stability is poor in extreme environments, resulting in the failure of the waterproof layer.

Method used

Using inorganic silicone deep penetration crystal waterproofing agent, the composite structure is formed to improve the penetration depth and the combination of modified zinc oxide particles and specific dispersants through the combination of raw materials such as active sodium silicate, nanocomposite particles and aluminate cement. Temperature and aging resistance.

Benefits of technology

It significantly improves the penetration depth and temperature resistance of waterproofing agent in concrete, ensures long-term waterproofing performance, and adapts to various application environments, reducing the formation speed and adhesion of the surface hydration layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of concrete waterproof materials, in particular to an inorganic silicon deep permeable crystallization waterproof agent and a preparation process. The invention discloses an inorganic silicon deep permeable crystallization waterproof agent, which is prepared from the following raw materials in parts by mass: 40 to 60 parts of active sodium silicate, 20 to 35 parts of nano composite particles, 10 to 15 parts of aluminate cement, 1 to 3 parts of coagulation accelerator, 5 to 15 parts of dispersing agent, 3 to 5 parts of thickening agent, 0.1 to 0.3 part of preservative and 40 to 65 parts of deionized water. According to the inorganic silicon deep permeable crystallization waterproof agent and the preparation process provided by the invention, the finally prepared waterproof agent not only has excellent waterproof and anti-corrosion properties, but also can further improve the penetration depth, temperature resistance and aging resistance of the inorganic silicon waterproof agent in concrete; therefore, the waterproof agent has good long-term waterproof performance, can adapt to various application environments, and has very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete waterproofing materials, and in particular to an inorganic silicon deep-penetrating crystalline waterproofing agent and a preparation process thereof. Background Art

[0002] In modern buildings, the waterproof performance of concrete structures is crucial to ensure the durability and safety of buildings. As a porous material, concrete is prone to leakage when exposed to water or moisture for a long time, leading to problems such as corrosion of internal steel bars and loss of structural strength. Therefore, the development of efficient, environmentally friendly and long-lasting waterproof materials is an important demand of the construction industry.

[0003] At present, common waterproof materials on the market include organic waterproof coatings, asphalt-based waterproof materials and inorganic waterproof materials. Among them, inorganic silicone waterproofing agents have attracted much attention due to their unique advantages. Inorganic silicone waterproofing agents mainly react with free lime in concrete through silicate solution to form insoluble calcium silicate crystals, which can fill the pores and microcracks inside the concrete, thereby improving the density and waterproof performance of the concrete.

[0004] However, existing inorganic silicone waterproofing agents still have some problems in practical applications. For example, the penetration depth of traditional inorganic silicone waterproofing agents in concrete is relatively shallow, usually only penetrating within a few millimeters of the surface. This causes the waterproofing effect to gradually weaken over time, especially in the case of long-term water immersion, the waterproof layer is prone to failure; and under extreme environmental conditions, such as high temperature, low temperature, and strong acid and alkali environments, the stability of traditional inorganic silicone waterproofing agents is poor, which may cause the waterproof layer to crack or fall off, affecting the waterproofing effect.

[0005] Therefore, in order to effectively solve the above problems, the present application provides an inorganic silicon deep penetration crystalline waterproofing agent and a preparation process. The final waterproofing agent not only has excellent waterproof and anti-corrosion properties, but can also further improve the penetration depth of the inorganic silicon waterproofing agent in concrete as well as its heat resistance and aging resistance, thereby ensuring that the waterproofing agent has good long-term waterproofing properties and can adapt to various application environments, and has very excellent application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides an inorganic silicon deep penetration crystalline waterproofing agent, the raw materials of which are, in parts by mass: 40 to 60 parts of active sodium silicate, 20 to 35 parts of nano-composite particles, 10 to 15 parts of aluminate cement, 1 to 3 parts of coagulant, 5 to 15 parts of dispersant, 3 to 5 parts of thickener, 0.1 to 0.3 parts of preservative, and 40 to 65 parts of deionized water.

[0007] As a preferred solution, the mass ratio of the active sodium silicate, nanocomposite particles and aluminate cement is (45-55): (22-28): (12-15).

[0008] As a preferred solution, the mass ratio of the active sodium silicate, nanocomposite particles and aluminate cement is (48-52): (24-26): (14-15).

[0009] As a preferred solution, the modulus of the active sodium silicate is 2-4.

[0010] As a preferred solution, the modulus of the active sodium silicate is 2.5-3.5.

[0011] As a preferred solution, the nanocomposite particles are a composition of nano silicon dioxide and modified zinc oxide particles.

[0012] As a preferred solution, the mass ratio of the nano-silicon dioxide to the modified zinc oxide particles is (2.8-3.5): (1.5-2.5).

[0013] As a preferred solution, the mass ratio of the nano-silicon dioxide to the modified zinc oxide particles is (3-3.2): (1.9-2.3).

[0014] As a preferred solution, the average particle size of the nano-silicon dioxide is 40-60 nm.

[0015] As a preferred solution, the preparation method of the modified zinc oxide particles comprises the following steps: S1: adding zinc oxide and zirconium chloride to deionized water, adding succinic anhydride and isopropyl tri(dodecylbenzenesulfonyl) titanate, heating to 60-65°C and keeping warm for 3-4 hours, after completion, centrifuging and filtering the product, washing and drying to obtain pretreated particles; S2: mixing the pretreated particles with 1,4-phthalic acid and p-aminobenzoic acid, adding to DMF and stirring thoroughly, heating to 120°C and keeping warm for 3-4 hours; ~130℃, keep warm for 20~22h, after completion, cool the product naturally to room temperature, wash with DMF and anhydrous ethanol alternately 2~3 times to obtain pre-modified particles; S3: add the pre-modified particles and ammonia water to deionized water, add triethanolamine and deionized water solution of tetraethyl orthosilicate dropwise, the reaction temperature is 60~65℃, the addition time is 0.5~0.6h, keep warm at 70~75℃ for 1~1.5h after the reaction is completed, filter and wash to obtain.

[0016] As a preferred solution, the mass ratio of zinc oxide, zirconium chloride, succinic anhydride and isopropyl tri(dodecylbenzenesulfonyl) titanate is (0.6-1):(4-5):(1.5-1.8):(0.2-0.25).

[0017] As a preferred solution, the average particle size of the zinc oxide is 5-10 nm.

[0018] As a preferred solution, in the pretreated particles, the mass ratio of 1,4-phthalic acid to p-aminobenzoic acid is (3.5-4): (2-2.5): (1-1.5).

[0019] As a preferred solution, the mass ratio of the pre-modified particles, ammonia water, triethanolamine and tetraethyl orthosilicate is (5-5.5): (0.5-0.8): (0.1-0.15): (1.5-2).

[0020] As a preferred solution, the average particle size of the modified zinc oxide particles is 450-550 nm.

[0021] In this application, the modified zinc oxide particles and nano-silicon dioxide are compounded and added to greatly improve the waterproof and anti-corrosion properties of the waterproofing agent, and can also greatly improve the heat resistance, aging resistance and other properties of the waterproofing agent in application environments such as high temperature and high humidity. The modified zinc oxide particles prepared in this application can form a composite structure with framework particles as the internal core, zinc oxide as the external intercalation site, and finally coated with amorphous silicon oxide. The existence of this structure can not only form a guiding effect on water molecules through the hydroxyl effect of the surface intercalated particle sites, thereby assisting the water absorption effect of the central framework particles, but also form a rougher filling pore surface, and reduce the large particle pore size caused by the amplitude motion of the microparticles during the filling process, thereby reducing the pore size, increasing the resistance to water molecule penetration and the length of the penetration path, thereby greatly improving the waterproof and anti-corrosion properties, while maintaining excellent service life, and greatly reducing the formation speed and adhesion of the surface hydration layer.

[0022] On the other hand, through the combined effect of the specifically selected compounded dispersant in the present application, the carrier multi-layer membrane structure of the compounded dispersant can greatly increase the fixing effect of the waterproofing agent in the concrete, enhance the deep penetration effect, and thus realize the crystal filling of the waterproofing agent inside the deep layer, thereby improving the overall performance while improving the stability of the waterproofing agent particles, avoiding the segregation and migration of the waterproofing agent after use, and thus having long-term aging resistance, waterproofness, heat resistance and other properties.

[0023] As a preferred solution, the density of the aluminate cement is 2.5-3 g / cm 3 .

[0024] As a preferred solution, the coagulant is at least one of calcium chloride, calcium nitrate, sodium carbonate, polyphosphate and aluminum sulfate.

[0025] As a preferred solution, the coagulant is aluminum sulfate.

[0026] As a preferred solution, the dispersant is a composition of C12~C14 fatty alcohol polyoxyethylene ether, tristyrylphenol polyoxyethylene ether and epoxy block polyether.

[0027] As a preferred solution, the mass ratio of the C12~C14 fatty alcohol polyoxyethylene ether and the epoxy block polyether is (3~3.5):(1~2):(6~8).

[0028] As a preferred solution, the hydroxyl value of the C12~C14 fatty alcohol polyoxyethylene ether is 70~90 mgKOH / g.

[0029] As a preferred solution, the C12~C14 fatty alcohol polyoxyethylene ether is an isomeric C13 fatty alcohol polyoxyethylene ether.

[0030] As a preferred solution, the weight average molecular weight of the epoxy block polyether is 2000~4000Da.

[0031] As a preferred solution, the ethylene oxide block content of the epoxy block polyether is 25-40wt%.

[0032] As a preferred solution, the HLB value of the tristyrylphenol polyoxyethylene ether is 16-18.

[0033] As a preferred solution, the thickener is at least one of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium polyacrylate, polyvinyl alcohol and sodium carboxymethyl cellulose.

[0034] As a preferred solution, the thickener is hydroxyethyl cellulose.

[0035] As a preferred solution, the preservative is at least one of sodium benzoate, potassium sorbate, methyl paraben, benzisothiazolinone and pentylene glycol.

[0036] As a preferred solution, the preservative is sodium benzoate.

[0037] As a preferred solution, the mass ratio of the coagulant to the thickener is (1.5-2.2): (3.5-4.8).

[0038] As a preferred solution, the mass ratio of the coagulant to the thickener is (2-2.2): (4-4.3).

[0039] As a preferred solution, the mass ratio of the nanocomposite particles to the dispersant is (22-28): (7-13).

[0040] As a preferred solution, the mass ratio of the nanocomposite particles to the dispersant is (24-26): (9-11).

[0041] The second aspect of the present application provides a preparation process of the above-mentioned inorganic silicon deep penetrating crystalline waterproofing agent, which specifically includes the following steps: S1: Mix active sodium silicate with part of deionized water, stir until completely dissolved to form a uniform mixed liquid, in another container, dry-mix the nano-composite particles, dispersant and aluminate cement, and then add the remaining deionized water to make it into a slurry to obtain a mixed slurry; S2: Slowly add the mixed slurry to the mixed liquid, stir with a high-speed stirrer at 800~1000rpm for 30~40min to ensure that the two components are fully mixed, and then add a coagulant, a thickener and a preservative in turn, and continue stirring for 5~10min after adding each material until all the ingredients are evenly distributed in the mixed liquid; S3: After the stirring is completely completed, pass the product through a 400~600 mesh sieve to remove large particles and impurities, and then transfer the product to a clean container and seal it for storage, avoid direct sunlight, and keep the temperature between 10℃~30℃.

[0042] The beneficial effects of this application are: 1. The inorganic silicon deep penetrating crystalline waterproofing agent provided in the present application not only has excellent waterproof and anti-corrosion properties, but also can further improve the penetration depth of the inorganic silicon waterproofing agent in concrete as well as its heat resistance and aging resistance, thereby ensuring that the waterproofing agent has good long-term waterproofing performance and can adapt to various application environments, and has very excellent application prospects. 2. An inorganic silicon deep penetrating crystalline waterproofing agent provided in the present application, the added modified zinc oxide particles can form a composite structure with framework particles as the internal core, zinc oxide as the external embedding site, and finally coated with amorphous silicon oxide. The existence of this structure can not only form a guiding effect on water molecules through the hydroxyl group action of the surface embedded particle sites, thereby assisting the moisture absorption effect of the central framework particles, but also form a rougher filling pore surface, and reduce the large particle pore size caused by the amplitude motion of the particles during the filling process, thereby reducing the pore size, increasing the resistance to water molecule penetration and the length of the penetration path, thereby greatly improving the waterproof and anti-corrosion properties while maintaining an excellent service life and greatly reducing the formation speed and adhesion of the surface hydration layer. 3. The inorganic silicon deep-penetrating crystalline waterproofing agent provided in the present application, the added modified zinc oxide particles can also work together with the dispersant specifically selected and compounded in the present application, and can greatly increase the fixing effect of the waterproofing agent in the concrete with the carrier multi-layer membrane structure of the compounded dispersant, enhance the deep penetration effect, and then can realize the crystal filling of the waterproofing agent inside the deep layer, thereby improving the overall performance while improving the stability of the waterproofing agent particles, avoiding the segregation and migration of the waterproofing agent after use, and thus having long-term aging resistance, waterproofness, heat resistance and other properties. DETAILED DESCRIPTION The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0043] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0044] Example 1 Example 1 The first aspect provides an inorganic silicon deep penetrating crystalline waterproofing agent, the raw materials of which are, by mass, 50.5 parts of active sodium silicate, 24.8 parts of nano-composite particles, 14.8 parts of aluminate cement, 2.1 parts of coagulant, 10.8 parts of dispersant, 4.2 parts of thickener, 0.16 parts of preservative and 55 parts of deionized water.

[0045] The modulus of the active sodium silicate is 2.8, and it was purchased from Tangshan Fengnan District Amway Chemical Co., Ltd., which sells a 2.6~3.5 modulus grade product.

[0046] The nano composite particles are a composition of nano silicon dioxide and modified zinc oxide particles, and the mass ratio of the nano silicon dioxide and modified zinc oxide particles is 3.2:2.

[0047] The average particle size of nano-silicon dioxide is 55nm.

[0048] The preparation method of modified zinc oxide particles comprises the following steps: S1: 0.8 parts of zinc oxide and 4.4 parts of zirconium chloride are mixed and added to 100 parts of deionized water, 1.6 parts of succinic anhydride and 0.24 parts of isopropyl tri(dodecylbenzenesulfonyl) titanate are added, the temperature is raised to 65°C and kept warm for 3 hours, after completion, the product is centrifuged and filtered, washed and dried to obtain pretreated particles; S2: 3.8 parts of pretreated particles are mixed with 2.2 parts of 1,4-phthalic acid and 1.4 parts of p-aminobenzoic acid, added to 120 parts of DMF and stirred thoroughly, Heat to 120°C and keep warm for 22 hours. After completion, cool the product naturally to room temperature, wash it alternately with DMF and anhydrous ethanol for 3 times to obtain pre-modified particles; S3: Mix 5.2 parts of pre-modified particles and 0.6 parts of ammonia water and add them to 180 parts of deionized water, add a deionized water solution containing 0.14 parts of triethanolamine and 1.8 parts of tetraethyl orthosilicate (40 parts in total) dropwise, the reaction temperature is 65°C, the addition time is 0.5h, keep warm at 70°C for 1.5h after the addition is completed, filter and wash after the reaction is completed, and the product is obtained.

[0049] The average particle size of zinc oxide is 8 nm; the average particle size of modified zinc oxide particles is 489 nm.

[0050] The density of aluminate cement is 2.8g / cm 3 , purchased from Zhengzhou Jinghua Special Cement Co., Ltd. for sale A700 model products.

[0051] The coagulant is aluminum sulfate; the thickener is hydroxyethyl cellulose; the preservative is sodium benzoate; The dispersant is a composition of isomeric C13 fatty alcohol polyoxyethylene ether, tristyrylphenol polyoxyethylene ether and epoxy block polyether, and the mass ratio of the three is 3.5:1.5:7.

[0052] The hydroxyl value of isomeric C13 fatty alcohol polyoxyethylene ether is 75 mgKOH / g, and the product was purchased from Haian Guoyun Chemical Co., Ltd. as model E-1312.

[0053] The weight average molecular weight of the epoxy block polyether is 3000 Da, and the L64 type ethylene oxide-propylene oxide block polyether product purchased from BASF in Germany has an ethylene oxide block content of 38 wt%.

[0054] The HLB value of tristyrylphenol polyoxyethylene ether is 17.4.

[0055] The second aspect of the present embodiment provides a preparation process of the above-mentioned inorganic silicon deep penetrating crystalline waterproofing agent, which specifically includes the following steps: S1: Mix active sodium silicate with part of deionized water, stir until completely dissolved to form a uniform mixed liquid, in another container, dry-mix the nano-composite particles, dispersant and aluminate cement, and then add the remaining deionized water to make it into a slurry to obtain a mixed slurry; S2: Slowly add the mixed slurry to the mixed liquid, stir at 1000rpm with a high-speed stirrer for 35 minutes to ensure that the two components are fully mixed, and then add a coagulant, a thickener and a preservative in turn, and continue stirring for 8 minutes after adding each material until all the ingredients are evenly distributed in the mixed liquid; S3: After the stirring is completely completed, pass the product through a 450-mesh sieve to remove large particles and impurities, and then transfer the product to a clean container and seal it for storage, avoid direct sunlight, and keep the temperature between 10°C and 30°C.

[0056] Example 2 The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the inorganic silicon deep penetrating crystalline waterproofing agent, in parts by mass, comprises the following raw materials: 55 parts of active sodium silicate, 22.2 parts of nano-composite particles, 12.4 parts of aluminate cement, 1.5 parts of coagulant, 7.8 parts of dispersant, 4.8 parts of thickener, 0.16 parts of preservative, and 58 parts of deionized water.

[0057] Example 3 The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the inorganic silicon deep penetrating crystalline waterproofing agent, in parts by mass, comprises the following raw materials: 45.5 parts of active sodium silicate, 27.5 parts of nano-composite particles, 15 parts of aluminate cement, 2.2 parts of coagulant, 12.6 parts of dispersant, 3.5 parts of thickener, 0.16 parts of preservative, and 60 parts of deionized water.

[0058] Comparative Example 1 The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the inorganic silicon deep penetrating crystalline waterproofing agent, in parts by mass, comprises the following raw materials: 65.5 parts of active sodium silicate, 10.5 parts of nano-composite particles, 20.5 parts of aluminate cement, 2.1 parts of coagulant, 10.8 parts of dispersant, 4.2 parts of thickener, 0.16 parts of preservative and 60 parts of deionized water.

[0059] Comparative Example 2 The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the inorganic silicon deep penetrating crystalline waterproofing agent, in parts by mass, comprises the following raw materials: 50.5 parts of active sodium silicate, 33.8 parts of nano-composite particles, 14.8 parts of aluminate cement, 2.1 parts of coagulant, 4.1 parts of dispersant, 4.2 parts of thickener, 0.16 parts of preservative and 60 parts of deionized water.

[0060] Comparative Example 3 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified zinc oxide particles comprises the following steps: S1: 0.2 parts of zinc oxide and 6.8 parts of zirconium chloride are mixed and added to 100 parts of deionized water, 1.8 parts of succinic anhydride and 0.35 parts of isopropyl tri(dodecylbenzenesulfonyl) titanate are added, the temperature is raised to 65°C and kept warm for 3 hours, after completion, the product is centrifuged and filtered, and the pretreated particles are obtained after washing and drying; S2: 4.2 parts of pretreated particles are mixed with 2.9 parts of 1,4-phthalic acid and 0.8 parts of p-aminobenzoic acid and added Add to 160 parts of DMF and stir thoroughly, heat to 120°C, keep warm for 22 hours, and naturally cool the product to room temperature after completion. Wash with DMF and anhydrous ethanol alternately for 3 times to obtain pre-modified particles; S3: Mix 5.2 parts of pre-modified particles and 0.6 parts of ammonia water and add them to 180 parts of deionized water, and add a deionized water solution containing 0.14 parts of triethanolamine and 1.8 parts of ethyl orthosilicate (40 parts in total) dropwise. The reaction temperature is 65°C, the dropping time is 0.5h, and the temperature is kept at 70°C for 1.5h after the dropwise addition is completed. After the reaction is completed, filter and wash to obtain.

[0061] The average particle size of the modified zinc oxide particles is 410 nm.

[0062] Comparative Example 4 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified zinc oxide particles comprises the following steps: S1: 2.5 parts of zinc oxide and 2.5 parts of zirconium chloride are mixed and added to 100 parts of deionized water, 1.1 parts of succinic anhydride and 0.18 parts of isopropyl tri(dodecylbenzenesulfonyl) titanate are added, the temperature is raised to 65°C and kept warm for 3 hours, after completion, the product is centrifuged and filtered, and the pretreated particles are obtained after washing and drying; S2: 3.8 parts of pretreated particles are mixed with 2.2 parts of 1,4-phthalic acid and 1.4 parts of p-aminobenzoic acid Add to 120 parts of DMF and stir thoroughly, heat to 120°C, keep warm for 22 hours, and naturally cool the product to room temperature after completion. Wash with DMF and anhydrous ethanol alternately for 3 times to obtain pre-modified particles; S3: Mix 4.2 parts of pre-modified particles and 0.9 parts of ammonia water and add them to 180 parts of deionized water, and add a deionized water solution containing 0.16 parts of triethanolamine and 3 parts of ethyl orthosilicate (40 parts in total) dropwise. The reaction temperature for dropwise addition is 65°C, the dropwise addition time is 0.5h, and the temperature is kept at 70°C for 1.5h after the dropwise addition is completed. After the reaction is completed, filter and wash to obtain.

[0063] The average particle size of the modified zinc oxide particles is 604 nm.

[0064] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 35 nm; and the average particle size of modified zinc oxide particles is 721 nm.

[0065] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that the dispersant is a composition of isomeric C13 fatty alcohol polyoxyethylene ether, tristyrylphenol polyoxyethylene ether and epoxy block polyether, and the mass ratio of the three is 8:5:3.

[0066] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that the hydroxyl value of the isomeric C13 fatty alcohol polyoxyethylene ether is 150 mgKOH / g, and the product is purchased from Hai'an Guoyun Chemical Co., Ltd. as model E-1304.

[0067] The weight average molecular weight of the epoxy block polyether is 1500 Da, and the L42 type ethylene oxide-propylene oxide block polyether product purchased from BASF in Germany has an ethylene oxide block content of 20 wt%.

[0068] Performance evaluation: Mechanical test: The flexural strength and compressive strength of the waterproofing agents prepared in the embodiments and comparative examples were tested with reference to the standard GB / T 18445-2012. The test values ​​were averaged from 10 tests and recorded in Table 1.

[0069] Waterproof test: Referring to the standard GB / T 18445-2012, the waterproofing agents prepared in the embodiments and comparative examples were subjected to anti-seepage and waterproofing tests, and the anti-seepage pressure was measured. The test values ​​were taken as the average value of 10 tests and recorded in Table 1.

[0070] Corrosion and heat resistance test: The waterproofing agents prepared in the examples and comparative examples were immersed in a 10wt% NaCl solution for 28 days, and the immersion temperature was maintained at 60±2°C. After the test was completed, the samples were taken out to observe whether there was obvious corrosion, damage, yellowing and cracking. If not, they were qualified, otherwise they were unqualified. 50 samples were tested in each group, and the qualified rate of the samples was recorded in Table 1.

[0071] Table 1 Performance test results It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 6 in terms of mechanical properties, waterproof and anti-corrosion properties, heat resistance and aging resistance. This is mainly due to the combined effect of the modified composite particles specified in the present application, the specific dispersant selection and other matching technical solutions. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests, which further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. An inorganic silicon deep penetrating crystalline waterproofing agent, characterized in that: The raw materials are, by weight: 40-60 parts of active sodium silicate, 20-35 parts of nanocomposite particles, 10-15 parts of aluminate cement, 1-3 parts of coagulant, 5-15 parts of dispersant, 3-5 parts of thickener, 0.1-0.3 parts of preservative, and 40-65 parts of deionized water; The modulus of the active sodium silicate is 2 to 4; The nanocomposite particles are a composition of nano silicon dioxide and modified zinc oxide particles; The mass ratio of the nano-silicon dioxide to the modified zinc oxide particles is (2.8-3.5): (1.5-2.5); The average particle size of the nano silicon dioxide is 40-60 nm; Preparation method of modified zinc oxide particles The following steps are involved: S1: Mix zinc oxide and zirconium chloride and add them to deionized water, add succinic anhydride and isopropyl tri(dodecylbenzenesulfonyl) titanate, heat to 60-65℃ and keep warm for 3-4h, after completion, centrifuge and filter the product, wash and dry to obtain pretreated particles; S2: Mix the pretreated particles with 1,4-phthalic acid and p-aminobenzoic acid and add them to DMF, stir thoroughly, heat to 120-130℃, keep warm for 20-22h, after completion, naturally cool the product to room temperature, wash with DMF and anhydrous ethanol alternately 2-3 times to obtain pre-modified particles; S3: Mix the pre-modified particles and ammonia water and add them to deionized water, add triethanolamine and deionized water solution of ethyl orthosilicate dropwise, the dropwise reaction temperature is 60-65℃, the dropwise addition time is 0.5-0.6h, after the dropwise addition is completed, keep warm at 70-75℃ for 1-1.5h, filter and wash after the reaction is completed, and obtain; The mass ratio of zinc oxide, zirconium chloride, succinic anhydride and isopropyl tri(dodecylbenzenesulfonyl) titanate is (0.6-1):(4-5):(1.5-1.8):(0.2-0.25); In the pretreated particles, the mass ratio of 1,4-phthalic acid to p-aminobenzoic acid is (3.5-4): (2-2.5): (1-1.5).

2. The inorganic silicon deep penetrating crystalline waterproofing agent according to claim 1, characterized in that: The mass ratio of the active sodium silicate, the nanocomposite particles and the aluminate cement is (45-55): (22-28): (12-15).

3. The inorganic silicon deep penetrating crystalline waterproofing agent according to claim 2, characterized in that: The average particle size of the zinc oxide is 5-10 nm.

4. The inorganic silicon deep penetrating crystalline waterproofing agent according to claim 3, characterized in that: The average particle size of the modified zinc oxide particles is 450-550 nm.

5. The inorganic silicon deep penetrating crystalline waterproofing agent according to claim 4, characterized in that: The density of the aluminate cement is 2.5-3 g / cm 3 .

6. The inorganic silicon deep penetrating crystalline waterproofing agent according to claim 5, characterized in that: The coagulant is at least one of calcium chloride, calcium nitrate, sodium carbonate, polyphosphate and aluminum sulfate.

7. The inorganic silicon deep penetrating crystalline waterproofing agent according to claim 6, characterized in that: The dispersant is a composition of C12~C14 fatty alcohol polyoxyethylene ether, tristyrylphenol polyoxyethylene ether and epoxy block polyether; the mass ratio of the C12~C14 fatty alcohol polyoxyethylene ether and epoxy block polyether is (3~3.5):(1~2):(6~8).

8. The inorganic silicon deep penetrating crystalline waterproofing agent according to claim 7, characterized in that: The hydroxyl value of the C12-C14 fatty alcohol polyoxyethylene ether is 70-90 mgKOH / g; the HLB value of the tristyrylphenol polyoxyethylene ether is 16-18.

9. The process for preparing the inorganic silicon deep penetrating crystalline waterproofing agent according to claim 8, characterized in that: The weight average molecular weight of the epoxy block polyether is 2000-4000 Da; the ethylene oxide block content of the epoxy block polyether is 25-40 wt %.

10. A process for preparing the inorganic silicon deep penetrating crystalline waterproofing agent according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Mix active sodium silicate with part of deionized water, stir until completely dissolved to form a uniform mixed liquid. In another container, dry-mix the nanocomposite particles, dispersant and aluminate cement, and then add the remaining deionized water to make a slurry to obtain a mixed slurry. S2: Slowly add the mixed slurry to the mixed liquid, stir with a high-speed stirrer at 800-1000rpm for 30-40min to ensure that the two components are fully mixed, then add the coagulant, thickener and preservative in turn, and continue stirring for 5-10min after adding each material until all the ingredients are evenly distributed in the mixed liquid. S3: After the stirring is completely completed, pass the product through a 400-600 mesh sieve to remove large particles and impurities, then transfer the product to a clean container and seal it for storage, avoid direct sunlight, and keep the temperature between 10℃ and 30℃.

Citation Information

Patent Citations

  • High-permeability concrete sealed waterproofing agent and preparation method thereof

    CN106565278A

  • Self-healing type anti-crack waterproof agent for concrete and preparation method of self-healing type anti-crack waterproof agent

    CN117430359A

  • Water-based capillary crystalline waterproof agent

    CN117777768A

  • Leakage-free solid drying agent special for electronic products and preparation method of leakage-free solid drying agent

    CN118179220A

  • Surface treatment method of concrete structure for water and sewage

    KR102167716B1